Development And Implication Of Gender And Women’s Studies Curriculum At Public Universities Of Punjab - Noreen, Saima; Deeba, Farah (2016)
In mid of the twentieth century, feminist movement commenced the discipline of women’s studies to encounter the Ideological critique; a theoretical framework lacking laborious struggle. This study is based on curriculum development and concepts, which were discussed in the process of curriculum making of Gender and Women’s studies in the Punjab. This study aimed to explore the process of curriculum development at graduation and post-graduation level with details of its updating, reading trends in students, teaching methodologies, and inclination of students towards research areas. A qualitative method of Interpretative Phenomenological Analysis (IPA) was used. The data was collected through in-depth semi-structured interviews from 15 participants. The interviewee included the head of Gender Studies Departments and faculty members of 6 universities and 1 college of the Punjab province of Pakistan. The data analysis indicated that each academic institution has similar process of curriculum development involving faculty, the Board of Studies and Academic Council. Curriculum is being revised on ongoing basis. In most of the departments, participatory and interactive teaching methods are being used. Reading habits are not greatly instilled among students. This research intended to trace out the locale of formative phase of main themes and fibers of courses in relation with indigenous gender tendencies. The study has suggested that acute involvement of development sector should be promised which will stage the local gender issues and will also open up a maiden window to academic side in the formulation of a more congenial and endemic syllabus.